Emotional Well-being and Second Language Acquisition Experiences among Adolescent Girls in Sampled Public Primary Schools in Kilifi County, Kenya - Anika, Alice A. (European Journal of Applied Sciences, 2026)
The emotional well-being of adolescent girls is often influenced by societal expectations, gender roles, and educational opportunities, especially in learning English as a second language. Nonetheless, despite efforts to promote gender equality and improve access to education, adolescent girls still encounter substantial barriers that affect their second language acquisition of English, which is the language of instruction in Kenyan schools. This study aimed to examine the ongoing challenges faced by adolescent girls in learning English, which are intensified by societal pressures and limited resources, ultimately affecting their overall educational experiences and emotional well-being. The research employed a mixed-methods design with a sample of 380 participants, stratified by grade level, including Grade 7 students aged 12 enrolled in public primary schools in Kilifi County, Kenya. The Warwick-Edinburgh Mental Well-being Scale (WEMWBS), the Rosenberg Self-esteem scale, and the Generalized Anxiety Disorder scale (GAD-7) were used to evaluate emotional well-being. Assessments for English Proficiency (AEP), which included self-assessments, frequency scales, and focus group discussions, were also conducted to measure English language acquisition skills through various classroom activities that assessed second-language learning experiences. Data analysis involved regression and thematic analysis. Results revealed a strong positive correlation (r = 0.65, p < 0.01) between second-language proficiency and self-esteem, suggesting that higher proficiency is associated with higher self-esteem among adolescent girls. A moderate negative correlation (r = -0.52, p < 0.01) was found between second-language proficiency and anxiety levels, while a moderate positive correlation (r = 0.58, p < 0.01) existed between second-language proficiency and social connectedness. Additionally, a strong positive correlation (r = 0.70, p < 0.01) was observed between second-language proficiency and overall life satisfaction, indicating that girls with greater proficiency tend to report higher life satisfaction. The socio-psychological effects on girls included high emotional trauma, anxiety, depression, stigma, bullying, low English proficiency scores, and shyness during oral English presentations. Traumatic experiences related to learning English as a second language were found to hinder adolescents' ability to reach their educational goals, leading to poor grades and discouragement from attending classes. The findings inform policies addressing traumatic experiences of adolescent girls learning English as a second language, including their impact on educational goals and the country's economic development. Additionally, they highlight the need to adopt the Mindfulness Model of Emotional Well-being in learning English as a second language among adolescent girls in schools.